A procedure for calculating the thermal constants associated with the flight period of Cerambyx welensii Küster and Prinobius myardi Mulsant from field observations. (6th November 2015) - López‐Pantoja, Gloria; Domínguez Nevado, Luis; Sánchez‐Osorio, Israel
Abstract: Field observations conducted in a dehesa in the southwest of the Iberian Peninsula over a period of 8 years (2002–2009) allowed the development and validation of two degree‐day phenology models for predicting the flight period of Cerambyx welensii Küster (1846) and Prinobius myardi Mulsant (1892). The start dates and functional development temperatures for the two species were estimated using an iterative method. The start dates were found to be 1 April for C. welensii and 15 April for P. myardi . The minimum development temperature for both species was 12 °C. The thermal constants associated with each flight percentage studied (1–99% at 10% intervals) were calculated from Gompertz curves fitting the equation CPE = exp [− exp (3.97 + 0.009DD)] ( r 2 = 0.955) for C. welensii and CPE = exp [− exp (6.50–0.008DD)] ( r 2 = 0.817) for P. myardi, where CPE is the cumulative percentage of emergence and DD is degree‐days . The validation procedure revealed that the proposed models predict cumulative flight percentages with errors of 2.5–4.3 days for C. welensii and 3.2–18.2 days for P. myardi The simplicity of the proposed method for calculating thermal constants and the small errors with which they can be estimated allow the widespread use of the models for efficiently managing populations of the two xylophagous cerambycids under study. This can be incorporated into a useful and novel element in the fight against the deterioration of a valuable ecosystem within the European Union.